On various ways of measuring pro-poor growth - Joseph Deutsch; Jacques Silber (Kiel Institute for the World Economy (IfW), 2011)
This paper examines three possible approaches to pro-poor growth. The first one assumes that the poverty line remains constant in real terms over time. The second perspective examines the case where the poverty line is equal to half the median of the income distribution but assumes that such a poverty line is determined exogenously. Finally the authors also propose a third type of decomposition of the change in poverty, one which is obtained when the poverty line is assumed to be endogenous. In addition, whatever the assumption made concerning the poverty line, the authors take both a relative and an absolute approach to inequality measurement when defining pro-poor growth. With a relative approach to pro-poor growth it is assumed that inequality does not to vary when all incomes are multiplied by a constant whereas, with an absolute approach to pro-poor growth, inequality is supposed not to vary when an equal sum is added to all incomes. The empirical illustration covers the period 1990-2006 in Israel and the analysis is based on the use of the FGT poverty index. It turns out that the assumptions made concerning the way the poverty line is defined and the choice between a relative and an absolute approach to pro-poor growth greatly affect the results. As a whole however growth was pro-rich in Israel during the 1990-2006 period.
Keywords: I32; O15; 330; inequality; Israel; pro-poor growth; Watts index